ComX-Induced Exoproteases Degrade ComX in Bacillus subtilis PS-216 - Spacapan, Mihael; Danevčič, Tjaša; Mandic-Mulec, Ines (Frontiers in Microbiology, 2018)
Gram-positive bacteria use peptides as auto-inducing (AI) signals to regulate the production of extracellular enzymes (e. g. proteases). ComX is an AI peptide, mostly known for its role in the regulation of bacterial competence and surfactant production in Bacillus subtilis. These two traits are regulated accordingly to the bacterial population size, thus classifying ComX as a quorum sensing (QS) signal. ComX also indirectly regulates exoprotease production through the intermediate transcriptional regulator DegQ. We here use this peptide based AI system (the ComQXPA system) as a model to address exoprotease regulation by ComX in biofilms. We also investigate the potential of ComX regulated proteases to degrade the ComX AI peptide. Results indicate that ComX indeed induces the expression of aprE, the gene for the major serine protease subtilisin, and stimulates overall exoprotease production in biofilms of B. subtilis PS-216 and several other B. subtilis soil isolates. We also provide evidence that these exoproteases can degrade ComX. The ComX biological activity decay is reduced in the spent media of floating biofilms with low proteolytic activity found in the comP and degQ mutants. ComX biological activity decay can be restored by the addition of subtilisin to such media. In contrast, inhibition of metalloproteases by EDTA reduces ComX biological activity decay. This suggests that both serine and metalloproteases, which are induced by ComX, are ultimately capable of degrading this signaling peptide. This work brings novel information on regulation of exoproteases in B. subtilis floating biofilms and reveals that these proteolytic enzymes degrade the AI signaling peptide ComX, which is also a major determinant of their expression in biofilms